2020
DOI: 10.1177/0093854820915740
|View full text |Cite
|
Sign up to set email alerts
|

Is Risk-Need-Responsivity Enough? Examining Differences in Treatment Response Among Male Incarcerated Persons

Abstract: Research examining the efficacy of cognitive behavioral therapy (CBT) in reducing recidivism has paid little attention to treatment factors contributing to response variability. Using an archival sample of 448 participants exposed to a risk-need-responsivity (RNR)-informed CBT program or no treatment, a multigroup latent profile analysis yielded a four-profile solution: a treatment-nonresponsive group and three treatment-responsive groups. Among the treatment-responsive profiles, reduced criminal attitudes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Recent research suggests that current estimates of efficacy for CBT-informed RNR are likely overestimated. In a secondary analysis of (Bourgon & Armstrong, 2005), Lester et al (2020) found that approximately 24.11% of individuals exposed to 200 hr of treatment were nonresponsive, as indicated by posttreatment assessments of the acquisition of skills, changes in pro-criminal attitudes, and rates of recidivism. Moreover, in both the 100- and 200-hr dosage groups, observed estimates of treatment efficacy were sensitive to individual differences, whereby partial removal of members with a high response to treatment resulted in nonsignificant changes in rates of recidivism relative to the no-treatment group.…”
mentioning
confidence: 99%
“…Recent research suggests that current estimates of efficacy for CBT-informed RNR are likely overestimated. In a secondary analysis of (Bourgon & Armstrong, 2005), Lester et al (2020) found that approximately 24.11% of individuals exposed to 200 hr of treatment were nonresponsive, as indicated by posttreatment assessments of the acquisition of skills, changes in pro-criminal attitudes, and rates of recidivism. Moreover, in both the 100- and 200-hr dosage groups, observed estimates of treatment efficacy were sensitive to individual differences, whereby partial removal of members with a high response to treatment resulted in nonsignificant changes in rates of recidivism relative to the no-treatment group.…”
mentioning
confidence: 99%
“…These interventions should be coupled with ongoing, high‐quality cognitive behavioral therapy (CBT) given the potential of CBT to promote mental health and reduce psychological distress while incarcerated (Amoke et al., 2020), and even meaningfully reduce the likelihood of recidivism (Mpofu et al., 2018). CBT may be even more effective when incorporating a risk–need–responsivity (RNR) approach that accounts for the need of individualized assessments of risk and treatment motivation (Lester et al., 2020). For individuals with a history of TBI, therapy may need to be more intensive; responsive to their level of risk and specific needs; and delivered in a manner that is in harmony with their mental, physical, and cognitive abilities and resources.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to remember that diversity within the classes found in this study inevitably remains. The movement away from a one-size-fits-all approach is supported by a variety of studies that have found differential treatment responsiveness (e.g., Lester et al, 2020) and highlight the criticality of consideration of responsivity needs, in addition to criminogenic needs, such cultural factors (e.g., Melton et al, 2014; Wilson & Gutierrez, 2014). The present study’s classification system, consistent with prior research, similarly highlights the importance that providers consider and incorporate the inherent differences (both historical and dynamic) of this population when developing and modifying treatment plans.…”
Section: Future Researchmentioning
confidence: 99%